Indonesian Language Interference in the Kaili Language of the Rai Dialect in Sipeso, Sindue Tobata District, Donggala Regency - Abd. Razak; Lidya Amalia; Nur Latifah; Desi Ameliya Putri (Civiliza Publishing, Indonesia., 2026)
Indonesia is recognized as one of the most linguistically diverse countries in the world, with hundreds of regional languages spoken across its archipelago. This study aims to describe the forms of Indonesian language interference in the Rai dialect of the Kaili language used in daily community communication. This research employed a descriptive qualitative method. The data were collected through observation, recording, and note-taking techniques from speakers of the Rai dialect of the Kaili language. The data were analyzed by identifying, classifying, and describing the forms of interference found in the utterances. The results revealed four forms of interference, namely lexical, morphological, syntactic, and phonological interference. Lexical interference was indicated by the inclusion of Indonesian vocabulary in Rai dialect utterances. Morphological interference appeared in the use of word-formation elements influenced by Indonesian. Syntactic interference was reflected in sentence structures influenced by Indonesian patterns, while phonological interference appeared in sound changes in the speakers' utterances. The findings indicate that the simultaneous use of two languages in daily communication contributes to the occurrence of Indonesian language interference in the Rai dialect of the Kaili language.